Cryptocurrency as a secondary form of manifestation of finance virtualization - Borzenko, O.O.; Hlazova, A.B. (BUKETOV BUSINESS REVIEW, 2021)
Object: Object of the paper is to develop theoretical principles that reveal the content, functions and role of cryptocurrency as new, quite controversial means of settlements appeared in digital society. Cryptocurrency is studied as a secondary form of finance virtualization. The investigation is directed on cryptocurrency’s theoretical and practical aspects of functioning. Methods: The investigation used statistical and economic-mathematical methods to analyze the current trend of development in bank and non-bank payment systems. The authors collected data about legal status of cryptocurrencies, then the obtained data was analyzed according to its official status in developed and developing countries. Findings: It was found that the biggest non-bank electronic payment system PayPal, as a secondary form of virtualization manifestation it currently shows higher growth of rate than the biggest bank card payment system — VISA. The position of cryptocurrencies in National Legal Systems of developed and developing countries was collected and analyzed, according to its legal status. The possible risks and controversial questions of cryptocurrency’s influence on price stability, stability of payment and financial systems are determined. Conclusions: Emergence of cryptocurrency in modern society is the evidence of global digitalization. Virtualization in its primary and secondary manifestation form affects financial sector. Secondary form of virtualization results in non-bank sector development, namely non-bank electronic payment systems (e.g., PayPal) and non-institutional digital schemes of settlements (cryptocurrency). Developed countries are mostly more progressive in cryptocurrency regulation than developing countries. In the case of global cryptocurrency spreading wide there are some risks national economies may face. They include the problem of price stability, the stability of the financial system, the stability of payment systems. Generally, the authors substantiate the requirement for search of the complete definition of cryptocurrency that may be integrated into national legal system for further regulation and risks controlling.